Personal aspirations and brand engagement in self-concept. (15th January 2017) - Razmus, Wiktor; Jaroszyńska, Małgorzata; Palęga, Magdalena
Abstract: In studies on self–brand relations very little attention is devoted to the analysis of drivers which determine such relations. The article presents a study testing the way in which intrinsic and extrinsic personal aspirations are linked with brand engagement in self-concept (BESC). The results of a study on an age-diverse sample of consumers ( N  = 480) show that people who value extrinsic aspirations exhibit a higher tendency to include important brands as part of their self-concept. Intrinsic aspirations, such as self-acceptance, affiliation, and community feeling, are negatively associated with BESC. Of extrinsic aspirations, the only one related to BESC is striving for appealing appearance. The obtained results suggest that including important brands as part of one's self-concept stems from the desire to build and have a proper image. Highlights: A comprehensive psychological explanation of the motivational drivers for BESC There is a positive and direct relationship between extrinsic aspirations and BESC. Appealing appearance is positively and directly related to BESC. Intrinsic aspirations are negatively associated with BESC.